Production of High-Grade Magnesia by Chemical Processing Routes - Moorrees C (The Australasian Institute of Mining and Metallurgy, 1987)
The end uses of magnesia are determined by both its chemical and its physical proper- ties. There is seen to be an increasing need for products of high chemical purity. Prod- ucts containing 90-95 per cent MgO can be routinely produced by physical beneficiation and calcination of most magnesite ores, the dominant source of magnesia. However, pro- duction of grades containing more than 98 per cent MgO with low impurity levels is not readily achieved physically. Such products can only be readily produced by chemical processing techniques. This presentation outlines the types of impurities present in magnesite deposits and the general concepts that are involved in chemically upgrading them. Of the potential leachants, only hydrochloric acid and aqueous carbon dioxide appear to be commercially attractive.